PERENCANAAN PERBAIKAN KERUSAKAN FLEXIBEL PAVEMENT PADA TAXIWAY B DAN C DI BANDAR UDARA KELAS 1 KALIMARAU BERAU - Mohammad Afandi Prawiro; Cahyaning Setyarini; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Kalimarau Berau Airport has a runway dimension of 2250 mx 45 m and has 3 taxiways, namely taxiways A, B and C, but taxiway A is included in the TNI area, Kalimarau Airport uses taxiways B and C. Conditions of taxiways B and C at Kalimarau Airport currently experiencing problems in the form of material loss and cracks. Therefore, an appropriate repair process must be carried out. The purpose of repairing pavement damage is to restore the strength of the pavement so that it can support the load of the aircraft. The level of damage to Taxiway B and C is calculated using the PCI method. The Budget Plan uses the 2021 Unit Price List in the related location (Berau, East Kalimantan.). The calculation of the level of damage using the PCI method, the results of the damage that exist on the entire surface of the taxiway are severe to light damage, and what needs to be repaired is for taxiway B, which is the location of damage number 1,3 and 5 and taxiway C is the location of damage number 1 and 6 , because there are only a few points that are damaged, the right repair is by patching. The calculation of RAB in planning for patching taxiways at Kalimarau Berau Airport is Rp. 372,832,774 (three hundred and seventy-two million eight hundred and thirty-two thousand seven hundred and seventy-four rupiah).